The dual role of thrombospondin-1 in inflammatory regulation during acute respiratory distress syndrome: a mini-review - Zheng, YaWen; Liu, Cong; Li, YaJun; Wang, WenFei; Dou, QingLi (Frontiers in Immunology, 2025)
Inflammation serves as a fundamental defense against tissue injury and infection, yet dysregulation can lead to pathological outcomes. Thrombospondin-1 (Thbs1/TSP1), a multifunctional glycoprotein significantly upregulated during inflammation, exemplifies a dualistic regulator with context-dependent roles. Through modulation of cytokine networks and inflammatory cell activity (notably macrophages), Thbs1 critically governs inflammatory responses. Acute respiratory distress syndrome (ARDS), a life-threatening condition fueled by systemic inflammation secondary to infection or trauma, presents complex pathophysiology requiring elucidation. COVID-19 research highlights elevated Thbs1 expression in severe patients, where it demonstrates protective effects against pulmonary damage primarily via extracellular matrix protection, inhibition of neutrophil serine proteases, and TGF-β-dependent repair pathways. However, paradoxical evidence indicates that dysregulated Thbs1 can also contribute to ARDS pathogenesis, potentially by amplifying inflammation, promoting thromboinflammation, or driving fibrosis. Mechanistic insights reveal Thbs1’s influence on ARDS progression through ECM remodeling, serine protease inhibition, and TGF-β activation. While significant progress has been made in understanding Thbs1 signaling, the precise mechanisms dictating its context-dependent switch between protective and pathogenic functions in inflammatory pathways remain a critical area for future investigation.